Professores de matemática diante da proposta curricular do estado de São Paulo (2008) - Oliveira, Joana Cristina de Souza (2013)
This research presents as an aim to analyse the impressions of a group formed by five Mathematics teachers about the State of São Paulo current curriculum implementation. It was elaborated in 2007 and implemeted in 2008 by the Department of the State of São Paulo (SEE/SP). The analysis is made from the subject speeches and the official documents available by the SEE/SP. As a background , we come up with the central ideas of some curriculum theories which are grounded in Doll (1997), Sacristán (2000), Sacristán (2007) and Silva (2011). These authors consider the curriculum as something that occurs in practice and that should be thought considering the educational system truth, in which teachers have a central and crucial function in the whole process. Thus , we perceive the curriculum as something constituted in practice, in the classroom. The issues that lead this research are: what do Mathematics teachers who act in basic education think about the implementation process of the Mathematics Curriculum Proposal PCM in 2008? What relation there can exist between what teachers say and what appears in official documents? The research is qualitative and can be characterized as a descriptive analytical. The meaning units were defined from the interviewed answers and from the official documents, the National Plan for Education (PNE), the Political Educational of the Government of the State of São Paulo Plan (2007), São Paulo Faz Escola magazine special edition of the Curriculum Proposal: Mathematics (2008), Mathematics Curriculum Proposal (2008), Manager Book (2009) and the Curriculum Proposal for First Grade Teaching Mathematics (2002). Among the obtained results we detach that the Curriculum Proposal of the State of São Paulo gives emphasis to external evaluations, which presentation and implementation have occurred by the managers. We also realized some contradictions between the teachers reports about what happens in the practice and what the developers argue. As well as between what appears in the documents and what happened in the educational institutions according to the teachers.